Access To Capital: Limitations For Small Fisherman In Gudang Lelang, Bandar Lampung City - Maloring, Darius Sesario; Damai, Abdullah Aman; Rochana, Erna; Riantini, Maya; Febryano, Indra Gumay (Journal of Tropical Marine Science, 2025)
Access to capital is very important in the development of small fishery businesses. This study aims to analyze the access to the capital of small fishermen in Bandar Lampung City Gudang Lelang. The research method uses a qualitative approach with a case study method. Data was obtained by in-depth interviews, participant observation, and document analysis; Furthermore, it was analyzed to explain the access to capital of small fishermen. The results of the study show that most small fishermen have difficulties accessing capital through banks. Most of them access non-formal capital, such as mobile lending, a door-to-door system known as bank keliling, loan sharks, Madani Mekaar National Capital, Syariah National Retirement Savings Bank, and Amartha. In addition, fishermen were used to borrowing money from skippers, subscription stalls, or their families to meet their needs at sea. They need the government’s support and mentoring in accessing bank capital to develop their businesses. Capital difficulties for fishermen’s businesses should be evaluated by banks to provide a more flexible system that is easily accessible.